Expansion of the market for AsSalwa honey MSMEs through product packaging automation and digital marketing - Eko Muh Widodo; Muhammad Resa Arif Yudianto; Rofi Abul Hasani (Community Empowerment, 2023)
This community service initiative leverages modern technology to enhance the efficiency and quality of AsSalwa honey production, as well as to improve the management of honey product sales. The method involves disseminating the use of filling machines and financial management systems. This program offers multiple benefits, including increased productivity in honey filling, maintaining a more consistent product quality, and providing access to accurate and detailed sales data through a Point of Sale (POS) system. The results obtained from this program demonstrate that honey owners can automatically fill honey into various packaging sizes using a filling machine. This machine is capable of filling liquid honey ranging from 100g to 2,500g. Additionally, the process of recording buying and selling transactions becomes more structured and well-documented. Partners can also estimate the profits obtained through one of the system's features. Through the combination of automatic filling and a POS system, this program has successfully improved product quality and enhanced the management capabilities of the honey business.